Assessing pain in children in the perioperative setting. Issue 1 (January 2019) - Bennett, Michelle
Pain assessment and management in children is challenging for a number of reasons. This paper aims to identify these challenges and highlight strategies for effective pain assessment and management in children in the perioperative setting.